EFFICIENCY ESTIMATION PROCEDURE OF INFORMATION PROTECTION MEANS FROM LEAKAGE ON OPTICAL CHANNELS - T. V. Borbotko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Efficiency estimation procedure of the spectroscopic-polarisation simulators applied to concealment of land object is offered. It allows to count a picking-up range and the recognition of object on the basis of laboratory examinations effects of protection means spectroscopic luminance factor and known value of spectroscopic luminance factor of a ground surface on which the hidden object is disposed.